Research competencies from the socio-formative approach in postgraduates from Peru and Ecuador - Garro-Aburto, Luzmila Lourdes; Romero-Vela, Sonia Lidia; Majo-Marrufo, Helga Ruth; Alcas-Zapata, Noel; Guerra-Reyes, Frank Edison (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The study sought to evaluate the levels of mastery of research competencies in postgraduate students from Peru and Ecuador from a socio-formative pedagogical approach. It was developed under the deductive method of descriptive scope. The analysis of the results places the postgraduates of both countries in the medium or resolutive level, which indicates that there are acceptable and sufficient competencies for research, but they do not manage to express themselves efficiently or in a creative and innovative manner. Likewise, there are limitations in dealing with different competencies inherent to scientific research.